Ultrastructural defects in stereocilia and tectorial membrane in aging mouse and human cochleae. Issue 9 (24th November 2019) - Bullen, Anwen; Forge, Andrew; Wright, Anthony; Richardson, Guy P.; Goodyear, Richard J.; Taylor, Ruth
Abstract: The aging cochlea is subjected to a number of pathological changes to play a role in the onset of age‐related hearing loss (ARHL). Although ARHL has often been thought of as the result of the loss of hair cells, it is in fact a disorder with a complex etiology, arising from the changes to both the organ of Corti and its supporting structures. In this study, we examine two aging pathologies that have not been studied in detail despite their apparent prevalence; the fusion, elongation, and engulfment of cochlear inner hair cell stereocilia, and the changes that occur to the tectorial membrane (TM), a structure overlying the organ of Corti that modulates its physical properties in response to sound. Our work demonstrates that similar pathological changes occur in these two structures in the aging cochleae of both mice and humans, examines the ultrastructural changes that underlie stereocilial fusion, and identifies the lost TM components that lead to changes in membrane structure. We place these changes into the context of the wider pathology of the aging cochlea, and identify how they may be important in particular for understanding the more subtle hearing pathologies that precede auditory threshold loss in ARHL. Abstract : We have described and investigated the pathologies of aging cochlea in both mice and humans to identify where aging pathologies are similar and different between the two. We have identified common pathological changes that are likely to have significant effects on hearing, improving the understanding of age‐related hearing loss.